Sectarian functioning and violence towards children: The case of the Baptist Church of Windsor - Pacheco, Adriana; Casoni, Dianne (Criminologie, 2022)
A case study of the Baptist Church of Windsor, this article looks at the church’s evolution from a dissident religious group in Quebec into an isolated sectarian group that believed in corporal punishment for children – punishment so severe it was considered child abuse by both the Quebec Office of the Attorney General and Quebec child protection services. The group’s history from foundation to dissolution was reconstructed through an exhaustive documentary analysis as well as the testimony of former members and interviews with key participants. Four stages in the group’s evolution were identified and analyzed, highlighting the elements that contributed to the development of a sectarian doctrinal context in which severe physical punishment against children was generally accepted as legitimate.